Of barriers to entry for medium and large n multiple streams applications: methodological and conceptual considerations - Engler, Fabian; Herweg, Nicole (Policy studies journal, 2019)
Recent literature reviews on contributions applying the multiple streams framework (MSF) concluded that although the framework is prolific, there is a lack of contributions testing it in a larger sample size. By addressing which barriers to entry medium and large n MSF applications face and by suggesting ways to handle them, we aim at providing researchers with a benchmark contribution for developing MSF-guided research designs based on a medium to a high number of cases. Building on an overview of the few existing medium and large n MSF studies, we address three challenges researchers must deal with: (1) choice of dependent variables and case selection; (2) operationalization and measurement of the framework's (predominantly figurative) key concepts; and (3) choice of a method that corresponds with the framework's research questions. In the latter regard, we focus on the pros and cons of employing regression analysis and qualitative comparative analysis. We conclude that although the barriers to entry are high for testing the MSF in a larger sample size, they are not insurmountable.